DETERMINATION OF THE ADSORPTION CAPABILITY OF ACTIVATED CARBON DERIVED FROM ZIZIPHUS MAURITIANA FOR THE REMOVAL OF LEAD AND COBALT (FUDMA JOURNAL OF SCIENCES, 2020)
This study was carried out to evaluate the efficiency of the removal of meals ions (Pb and Co) of metals ions (Pb and Co) from solution using Ziziphus mauritiana as adsorbent. The effect of initial concentration and adsorbent dosage on the adsorption process of these metals were studied, the percentage removal of these metals increased with increase in weight of carbon dosages (0.5 - 2.5g) in 50ml of the solution and the adsorption efficiency increased with increasing initial metal ion concentration (0.01-0.05 moldm-3), the optimum percentage removal of the was found to be 62% and 60% for Pb and Co respectively at the highest weight (2.5g). The adsorption fitted to Langmuir models and the coefficients indicated favorable adsorption of Pb2+ and Co2+ ions on the adsorbents. The adsorption of Pb2+ and Co2+ in aqueous solution was in the following order (1400µm>420µm>150µm). In this study more than 55.4% of lead cations were removed by 1400µm, 47.2% by 420µm and 29.8% by 150µm respectively. While for cobalt cations only 53.2% by 1400µm, 38.6% by 420µm and 24% by 150µm respectively. Therefore, lead can be better using activated carbon derived from Ziziphus mauritiana seed.
Keywords: Adsorption, Carbon, Cobalt, Lead, Ziziphus mauritiana